Executive Director’s Message - Harley, Catherine (Operating Room Nurses Association of Canada Journal, 2012)
The Operating Room Nurses Association of Canada (ORNAC) has, throughout 2012, been working on the implementation of a five year strategic plan to better meet the future needs of Perioperative Registered Nurses. A key priority, identified in the strategic plan, was the need to strengthen ORNAC’s Governance. ORNAC formed a team along with Pat Pocock, Co-Chair of the ORNAC Advocacy Pillar, and Karen Cooper, a lawyer with the Ottawa law firm Carters Professional Corporation, to develop the ORNAC Articles of Continuance and align the ORNAC Bylaws with the new Canada Not-For-Profit Corporations Act that came in to force in October 2011. Restructuring of the ORNAC Board (reducing the number from 28 to 17) was necessary in order to meet the requirements of this act. This restructuring has been taken into consideration in the development of the new bylaws. The Articles of Continuance and the new ORNAC Bylaws will be voted on, by the provincial members, at the April 2013 Annual Members Meeting in Ottawa.